2019
DOI: 10.3390/w12010011
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Changes of Water Yield in Qinghai Lake Watershed of China

Abstract: Water yield is an important ecosystem service, which is directly related to human welfare and affects the sustainable development. Using the integrated valuation of environmental services and tradeoffs model (InVEST model), we simulated the dynamic change of water yield in Qinghai lake watershed, Qinghai, China, and verified the simulation results. This paper emphatically explored how precipitation change and land use/land cover change (LUCC) affected the change of water yield on the spatial and temporal scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 48 publications
(56 reference statements)
7
15
0
Order By: Relevance
“…In addition, within each slope grade, water yield initially increased and then gradually decreased over time, with a peak in 1989. In general, topographical factors indirectly affect the water yield ecosystem service function by affecting precipitation and vegetation types, as also reported by Lian et al (2020) .…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…In addition, within each slope grade, water yield initially increased and then gradually decreased over time, with a peak in 1989. In general, topographical factors indirectly affect the water yield ecosystem service function by affecting precipitation and vegetation types, as also reported by Lian et al (2020) .…”
Section: Discussionsupporting
confidence: 60%
“…The water yield of Shangri-La City generally showed significant changes corresponding to changes in precipitation and evapotranspiration, with the effect of precipitation on water yield far exceeding that of PET. Many past studies have similarly shown that a decrease in precipitation results in corresponding decreases in water yield ( Lian et al, 2020 ) and that precipitation is considered to be an important factor affecting changes in water yield ( Li et al, 2021b ; Yang et al, 2021 ). Evapotranspiration is a key component of the terrestrial water cycle connecting the atmosphere, vegetation, and soil, and represents the sum of vegetation and soil evaporation ( Yin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Land use influences carbon sequestration [56] and soil conservation directly [57], and it also influences water yield by hydrologic processes [58]. Similarly, precipitation is the key factor for carbon sequestration [59], soil conservation [60], and water yield [61]. Soil properties affect plant growth [62], soil erosion [63], and hydrologic processes [64], and they are also important factors for these three ESs.…”
Section: The Limitation Of the Methods And Resultsmentioning
confidence: 99%